Synergy Development of â€œState-Representative Apparatusâ€ in Accelerating Social Forestry Policy Outcomes in Ngawi Regency, East Java - Ragandhi, Arsad (Cakrawala, 2021)
Social forestry is a new approach to solving problems around forests, such as poverty, social inequality, and massive deforestation. Indonesiaâ€™s new social forestry policy has given local communities greater rights and legal certainty regarding their involvement in forest management. However, local communities cannot stand alone in their implementation but must collaborate with other relevant stakeholders. A qualitative descriptive approach is used in this paper to capture efforts to build synergies between stakeholders in forest management and empowerment of forest communities in Ngawi Regency and identify opportunities and challenges afterward. The results of our analysis found that the signing of the MoU can be the first step to accelerate the achievement of social forestry policy outcomes. The dichotomy between â€œforestâ€ and â€œsocialâ€ affairs is increasingly visible in the division of tasks of each stakeholder involved. There is a need for clear legal rules regarding the roles and limits of allowable intervention for Regency governments. In addition, an urgent issue that needs to be addressed is the acceleration of capacity building and the capability of local communities, which are identified as essential factors in the success of social forestry policies.